2021
DOI: 10.1016/j.molmet.2021.101349
|View full text |Cite
|
Sign up to set email alerts
|

The hepatocyte IKK:NF-κB axis promotes liver steatosis by stimulating de novo lipogenesis and cholesterol synthesis

Abstract: Objective Obesity-related chronic inflammation plays an important role in the development of Metabolic Associated Fatty Liver Disease (MAFLD). Although the contribution of the pro-inflammatory NF-κB signaling pathway to the progression from simple steatosis to non-alcoholic steatohepatitis (NASH) is well-established, its role as an initiator of hepatic steatosis and the underlying mechanism remains unclear. Here, we investigated the hypothesis that the hepatocytic NF-κB signaling pathway acts as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…In our work, we provide evidence to suggest that miR-379-5p negatively regulates STAT1 expression through transcriptional and post-transcriptional levels, showing the function of improving liver injury. HMGCS1 is one of the key enzymes in FC biosynthesis, and inhibiting its expression can reduce the FC synthesis pathway [ 39 ]. It has been reported that HMGCS1 is mainly regulated by SREBP2.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, we provide evidence to suggest that miR-379-5p negatively regulates STAT1 expression through transcriptional and post-transcriptional levels, showing the function of improving liver injury. HMGCS1 is one of the key enzymes in FC biosynthesis, and inhibiting its expression can reduce the FC synthesis pathway [ 39 ]. It has been reported that HMGCS1 is mainly regulated by SREBP2.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB seems to be the culprit in the production of inflammation in the lipid-overloaded environment [ 8 , 56 ]. The direct involvement of NF-κB in lipid regulation has been further demonstrated [ 37 , 57 , 58 ]. Hence, in this study, NF-κB signaling was examined by western blotting and found to be suppressed after WY-14,643 was administered, which is consistent with previous results [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of LDL in the serum increases and the level of oxLDL increases accordingly, which can activate NF-κB [ 30 ]. After the activation of NF-κB, on the one hand, it promotes the de-novo synthesis of cholesterol in the hepatocytes by inhibiting the AMPK pathway [ 31 ], and on the other hand, it inhibits the expression of PPARs. PPARs can reduce the level of TC7-hydroxylase (CYP7a1) in vivo [ 32 ].…”
Section: Inflammatory Response Associated With Hyperlipidemiamentioning
confidence: 99%